Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T20:15:04+01:00
A) 4(x³-2x²-5x+2)-x(2x²-3x+5)
4x³-8x²-20x+8-2x³+3x²-5x=2x³-5x²-25x+8
b) 2x(x²-3x+7)+3(x³-2x²+4)
2x³-6x²+14x+3x³-6x²+12=5x³-12x²+14x+12
c) 3(1½a-2b-¼c)-2(-3a-4½b-⅛c)
9/2a-6b-3/4c+6a+9b+1/4c=21/2a+3b-1/2c
d) 1½(2a-3b-c)-2½(a-2b+c)
3a-9/2b-1 1/2c-2 1/2a+5b-2 1/2c=1/2a+1/2b-4c
5 5 5
2010-02-02T20:19:24+01:00
A) 4x³-8x²-20x+8-2x³+3x²-5x=2x³-5x²-25x+8
b)2x³-6x²+14x+3x³-6x²+12=5x³-12x²+14x+12
c)4½a-6b-3¼c-2½a+5b-2⅛c=2a-b-5¼c
d)3a-4½b-1½c-2½a+5b-2½c=½a+½b-4c
3 5 3
2010-02-02T20:24:53+01:00
A) 4(x³-2x²-5x+2)-x(2x²-3x+5)=4x³-8x²-20x+8-2x³+3x²-5x=2x³-5x²-25x+8
b) 2x(x²-3x+7)+3(x³-2x²+4)=2x³-6x²+14x +3x³-6x²+12=5x³-12x²+14x+12
c) 3(1½a-2b-¼c)-2(-3a-4½b-⅛c)=3(3/2a-2b-1/4c)-2(-3a-9/2b-1/8c)=
9/2a-6b-3/4c+6a+9b+1/4c=10i1/2a+3b-1/2c
d) 1½(2a-3b-c)-2½(a-2b+c) =3/2(2a-3b-c)-5/2(a-2b+c)=
3a-9/2b-3/2c-5/2a+10b-5/2c=1/2a +5i1/2b-4c
(/---->oznacza kreskę ułamkową)
3 5 3